Patients presenting with acute coronary syndromes have unreported coronary artery calcium on historical CT imaging. (14th October 2021) - Bradley, C; Aggarwal, A; Goatman, K; Jones, G; Berry, C; Good, R
Abstract: Introduction: Ischaemic heart disease (IHD) remains the leading cause of mortality globally1. The presence and extent of coronary artery calcification (CAC) is a strong predictor of cardiovascular events, and CAC scoring has been shown to be more predictive of cardiovascular events than other traditional risk assessment scores2. Incidental coronary calcification can be detected and quantified on non-gated CT chest scans covering the heart in the field of view3. This finding is typically not reported4 and hence an opportunity to optimise cardiovascular risk assessment and treatment is missed. Purpose: We sought to investigate whether patients presenting to our centre with an acute coronary syndrome (ACS) event had historical CT imaging demonstrating coronary artery calcification. Methods: We retrospectively reviewed case records for all patients referred to our centre for an invasive coronary angiogram following their first known admission with an ACS event. ACS were defined according to contemporary guidelines from the European Society of Cardiology. We reviewed a 3 month period prior to the COVID-19 pandemic (01/01/2019–31/03/2019). The national imaging database was interrogated to identify previous CT imaging that includes the heart in the field of view. The presence of coronary calcification was confirmed and quantified using an ordinal scoring method previously described3. The clinical radiology reports for the scans were reviewed to determine the frequency of CAC being reported. Demographic information was collected from our electronic patient record including the presence of risk factors for IHD. Prescribed medication prior to admission was also recorded using the on-admission medicines reconciliation documented in the electronic patient record. Results: 385 patients with first presentation of ACS were identified. 75 (19%) had a prior non-gated CT chest imaging. The most common indication for CT was for investigation of possible malignancy. The mean interval from CT imaging to ACS admission was 36 months. CAC was present on 67 (89%) scans. The mean ordinal score was 4.04, corresponding to moderate CAC. The distribution of CAC by coronary artery revealed the majority of disease to involve the left anterior descending artery (Table 1). Only 12/67 (18%) of clinical radiology reports mentioned coronary calcification (Figure 1). Patients with CAC frequently had additional risk factors for IHD. Despite this only 42% were prescribed antiplatelet therapy, and only 45% prescribed a statin. Conclusions: A significant proportion of ACS admissions have evidence of CAC on historical CT scans. This finding is often not reported and the majority of patients with demonstrated coronary artery disease are not prescribed appropriate preventative therapies. Systematic reporting of this finding may have a significant impact on the prevention of acute cardiovascular events. Funding Acknowledgement: Type of funding sources: None.